Arctic Suicide, Social Medicine, and the Purview of Care in Global Mental Health - Trout, Lucas (Health Hum Rights, 2020)
Youth suicide is a significant health disparity in circumpolar indigenous communities, with devastating impacts at individual, family, and community levels. This study draws on structured interviews and ethnographic work with health professionals in the Alaskan Arctic to examine the meanings assigned to Alaska Native youth suicide, as well as the health systems that shape clinicians’ practices of care. By defining suicide as psychogenic on the one hand, and as an index of social suffering on the other, its solutions are brought into focus and circumscribed in particular and patterned ways. We contrast psychiatric and social explanatory models, bureaucratic and relational forms of care, and biomedical and biosocial models for care delivery. Within the broader context of global mental health, this study suggests steps for linking caregiving to the health and social equity agenda of social medicine and for operationalizing commitments to health as a human right.